2022
DOI: 10.1093/jxb/erac162
|View full text |Cite
|
Sign up to set email alerts
|

Biological soil crusts and how they might colonize other worlds: insights from these Brazilian ecosystem engineers

Abstract: When bryophytes, lichens, eukaryotic algae, cyanobacteria, bacteria and fungi live interacting intimately with the most superficial particles of the soil, they form a complex community of organisms called the biological soil crust (BSC or biocrust). These biocrusts occur predominantly in drylands, where they provide important ecological services such as soil aggregation, moisture retention and nitrogen fixation. Unfortunately, many BSC communities remain poorly explored, especially in the tropics. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 180 publications
0
2
0
Order By: Relevance
“…Together with these strategies, the soil fertility improvements by biocrusts make them excellent agents for practical applications to control desertification. 126 Recently, De Oliveira and Maciel-Silva 127 compared the Brazilian biocrust communities with that from different ecosystems and proposed the utilization of biocrusts as ‘ecosystem engineers’ for colonizing other ecosystems. The meta-analysis of the biocrusts suggested that the soil organic carbon (SOC) concentration increased by 70.9% compared to the uncrusted soil, and the random forest analysis showed that the total N was an essential determinant of the concentration of SOC, followed by climate ( p < 0.01).…”
Section: Microalgae and Cyanobacteria In Biological Soil Crusts: Sign...mentioning
confidence: 99%
“…Together with these strategies, the soil fertility improvements by biocrusts make them excellent agents for practical applications to control desertification. 126 Recently, De Oliveira and Maciel-Silva 127 compared the Brazilian biocrust communities with that from different ecosystems and proposed the utilization of biocrusts as ‘ecosystem engineers’ for colonizing other ecosystems. The meta-analysis of the biocrusts suggested that the soil organic carbon (SOC) concentration increased by 70.9% compared to the uncrusted soil, and the random forest analysis showed that the total N was an essential determinant of the concentration of SOC, followed by climate ( p < 0.01).…”
Section: Microalgae and Cyanobacteria In Biological Soil Crusts: Sign...mentioning
confidence: 99%
“…Due to their unique physiology and ecology, bryophytes serve as ecosystem engineers, providing important ecological services including nitrogen and carbon fixation (Barger et al, 2016; Benalp, 2001; Oliveira & Maciel‐Silva, 2022). It is quite clear that they differ from vascular species in influencing the cycling of elements and energy flow, but the metabolic strategies that make them such talented colonizers have been only partially explored (Degola et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The principal function of soil algal communities in promote soil formation and biochemical processes include dinitrogen fixation, stabilization of aggregates, mineralization of organic matter, elevate soil air and water retention capacity, improve soil microbial activity and structure, et al (Metting, 1981;Glaser et al, 2018;Alvarez et al, 2021). Thereafter, algae play an important role in soil and vegetation restoration in waste rock dumps and anthropogenically disturbed lands (Carvalhido et al, 2021;Oliveira and Maciel-Silva, 2022). Making clear soil algal community composition and its influencing factors in forest ecosystems is of great significance for better understanding their ecological functions.…”
mentioning
confidence: 99%